ERCP for severe acute cholangitis: The earlier, the better - Iyad Khamaysi; Rana Taha (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Khamaysi I, Taha R. ERCP for severe acute cholangitis: The earlier, the better. Turk J Gastroenterol 2020; 31(1): 78-9.